ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (Studi kasus pada wajib pajak PBB P2 Kecamatan Pesantren Kota Kediri) - Prihartanto, Christian Danang; Pusposari, Devy (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to understand the influence of SPPT, knowledge of taxation, tax service and tax payers awareness on tax payers obedient in paying riil property tax. Data obtained in the form of a questionnaire distributed primary data in the Pesantren Subdistrict, Kediri. Statistical method used multiple regression analysis. The result showed that the factors of SPPT, sanction, tax service and compass time has positive and significant influence both partially and simultaneously. Keywords : obedient of tax payers, SPPT, knowledge of taxation, tax service and tax payers awareness.